Modification of aromatic self-assembled monolayers by electron irradiation: basic processes and related applications - Yildirim, Can; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
The effect of electron irradiation on aromatic thiolate self-assembled monolayers (SAMs) with oligophenyl, acene, and oligo(phenylene ethynylene) (OPE) backbones, containing from one to three phenyl rings, was studied, with emphasis on the basic irradiation-induced processes and performance of these films as negative resists in electron lithography. All films exhibited similar behavior upon the irradiation, with clear dominance of cross-linking, taking hold of the systems at already very early stages of the treatment. The cross sections for the modification of the SAM matrix and the damage of the SAM-substrate interface were determined for the primary electron energy of 50 eV, frequently used for the fabrication of carbon nanomembranes (CNM). They show only slight dependence on the backbone character as demonstrated by the example of the three-ring films. The two-ring systems exhibited the best performance as lithographic resists, with an optimal dose of 10-20 mC/cm2 at 0.5-1 keV. The performance of the one-ring and three-ring systems was limited by a poor ability to form an extensive cross-linking network and by high resistance of the pristine films to the etching agents, respectively. Another process, associated with the poor lithographic performance of the three-ring systems but occurring at high doses for the two-ring systems as well, was a spontaneous release of the cross-linked films within the irradiated areas, in form of CNM pieces. From the lithographic data, cross sections of the irradiation-induced cross-linking were derived and discussed in context of backscattering and secondary electron yield. For the three-ring systems, fabrication of CNMs was demonstrated, for the first time in the OPE case.
Publication Date (Web): December 19, 2016
Gesehen am 03.07.2018